Concepts of Applied Art, Design and Architecture: Use of Technologies Coupled with Intuitive Processes and Procedures and Rationalized in Workshops-Laboratories for the Design and Materialization of Projects - Martins da Matta, Celio; Martins da Matta, Andre (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2017)
Process of study of two binomials considered inseparable: creative-rational and conceptualization-materialization. Translates the academic experience with classes, orientations, disciplines, coordination of laboratories and doctoral thesis: Artemídia Influente: Ateliê-Laboratório in the Interfaces Art, Science and Technology. This mixture provided information on laboratory tests for the conception, materialization and understanding of art and its derivatives in the art, science and technology interfaces. Emphasis on the use of materialization processes, which a priori served as a didactic tool and were subsequently used to make artistic works, concomitantly the awareness and scientific artistic appropriation of these didactic prototypes of courses in design, architecture and art.